2004
DOI: 10.1097/00000542-200406000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Interaction between Propofol and Remifentanil Regarding Hypnosis, Tolerance of Laryngoscopy, Bispectral Index, and Electroencephalographic Approximate Entropy

Abstract: Remifentanil alone is ineffective at ablating response to stimuli but demonstrates potent synergy with propofol. BIS and AE values corresponding to 95% probability of ablating response are influenced by the combination of propofol and remifentanil to achieve this endpoint, with higher propofol concentrations producing lower values for BIS and AE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
235
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(254 citation statements)
references
References 37 publications
11
235
3
5
Order By: Relevance
“…It was observed that considerable periods in dynamic conditions were obtained (approximately 50 % for each observed signal). The technique may be employed in search of combined periods of input and output SS, allowing the construction of surface models translating the relation between hypnotic and analgesic drugs and their impact on the output signals, under SS conditions, and under the influence of different stimuli intensities [33].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that considerable periods in dynamic conditions were obtained (approximately 50 % for each observed signal). The technique may be employed in search of combined periods of input and output SS, allowing the construction of surface models translating the relation between hypnotic and analgesic drugs and their impact on the output signals, under SS conditions, and under the influence of different stimuli intensities [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other combinations which can be used are ketamine [28], propofol [27], propofol with fentanyl ,propofol with remifentanyl [29],etc. Each has its own positive and negative points.…”
Section: Anaesthesia Section Discussionmentioning
confidence: 99%
“…Secondly, he thinks it unlikely that this was a case of inadvertent intravascular injection and was more likely to be one of local anaesthetic overdose. It is well recognised that inadvertent intravascular injection of local anaesthetic can occur despite all the precautions designed to prevent such an occurrence [3] and that toxicity can occur with a wide range of doses [4,5]. I would suggest that it is difficult to be absolutely certain that inadvertent intravascular injection did not occur in this case.…”
Section: A Replymentioning
confidence: 96%
“…Previous investigators have studied propofol in isolation however we know that propofol and remifentanil are subject to a complex interaction [3]. Finally, the authors might use their current data to calculate more appropriate values of ke0 for each of the parameters that they have reported and consider how these lie within the population of previous estimates.…”
Section: A Replymentioning
confidence: 99%